Cdc42p controls yeast-cell shape and virulence of Paracoccidioides brasiliensis - Almeida, A. J. (2009)
Paracoccidioides brasiliensis is characterized by a multiple budding phenotype and a polymorphic cell growth, leading to the formation of cells with extreme variations in shape and size. Since Cdc42 is a pivotal molecule in establishing and maintaining polarized growth for diverse cell types, as well as during pathogenesis of certain fungi, we evaluated its role during cell growth and virulence of the yeast-form of P. brasiliensis. We used antisense technology to knock-down PbCDC42's expression in P. brasiliensis yeast cells, promoting a decrease in cell size and more homogenous cell growth, altering the typical polymorphism of wild-type cells. Reduced expression levels also lead to increased phagocytosis and decreased virulence in a mouse model of infection. We provide genetic evidences underlying Pbcdc42p as an important protein during host-pathogen interaction and the relevance of the polymorphic nature and cell size in the pathogenesis of P. brasiliensis.